Evaluation of Recurrent Ovarian Cancer: An Evolution - Nawi, Norazlina Mat; Mohamad, Irfan (International Journal of Human and Health Sciences (IJHHS), 2019)
Ovarian cancer is one of the top five cancers among female. It is treated with surgery and chemotherapy. Besides the well-known tumor marker CA-125, the treatment response is monitored by radiological imaging. Computed tomography (CT) and magnetic resonance imaging are used to be the primary modalities. With the emergence of positron emission tomography (PET), the detection of residual or recurrence disease can be made more accurate. The fusion of PET/CT has higher sensitivity and specificity. International Journal of Human and Health Sciences Vol. 04 No. 01 January’20 Page : 15-18